2017
DOI: 10.3389/fpls.2017.01739
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Symbiosis Alleviates Salt Stress in Black Locust through Improved Photosynthesis, Water Status, and K+/Na+ Homeostasis

Abstract: Soil salinization and the associated land degradation are major and growing ecological problems. Excess salt in soil impedes plant photosynthetic processes and root uptake of water and nutrients such as K+. Arbuscular mycorrhizal (AM) fungi can mitigate salt stress in host plants. Although, numerous studies demonstrate that photosynthesis and water status are improved by mycorrhizae, the molecular mechanisms involved have received little research attention. In the present study, we analyzed the effects of AM s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
141
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(154 citation statements)
references
References 62 publications
(128 reference statements)
9
141
0
4
Order By: Relevance
“…Photosynthesis is a key physiological process known to be sensitive to salt stress (Chen et al . ). Previous studies have shown that ACh regulates plant growth and development processes mediated by phytochromes (Tretyn & Kendrick ).…”
Section: Discussionmentioning
confidence: 97%
“…Photosynthesis is a key physiological process known to be sensitive to salt stress (Chen et al . ). Previous studies have shown that ACh regulates plant growth and development processes mediated by phytochromes (Tretyn & Kendrick ).…”
Section: Discussionmentioning
confidence: 97%
“…salt stress (100 and 150 mM) and similar Gs values between different treatments at 200 mM salt. The lower reduction of Gs in mycorrhizal seedlings than nonmycorrhizal seedlings under moderate salt stress suggested that the growth status may be better in mycorrhizal seedlings, resulting from less of a decrease in CO 2 diffusion through the stomata [34]. The Ci values were higher than those under unstressed conditions, which may indicate that enzymes in the photosynthesis apparatus were destroyed, resulting in a decrease in CO 2 assimilation and the accumulation of CO 2 in intercellular areas [35].…”
Section: Plos Onementioning
confidence: 96%
“…This latter effect was partially reverted when the plants growing in sterile soils were inoculated with the AMF Funneliformis mosseae (Chialva et al, 2018), indicating a key role for that kind of root symbiont. Arbuscular mycorrhizal fungi also improved the general performance of Robinia pseudoacacia seedlings under stress by NaCl salt (Chen et al, 2017). The overall physiological status of the plants (photosynthetic rate, photosystem II quantum efficiency and relative water content) was boosted by the symbiont, at the time that genes encoding membrane transport proteins involved in K + /Na + homeostasis in roots were found to be upregulated (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Arbuscular mycorrhizal fungi also improved the general performance of Robinia pseudoacacia seedlings under stress by NaCl salt (Chen et al, 2017). The overall physiological status of the plants (photosynthetic rate, photosystem II quantum efficiency and relative water content) was boosted by the symbiont, at the time that genes encoding membrane transport proteins involved in K + /Na + homeostasis in roots were found to be upregulated (Chen et al, 2017). Although AMF is by far one of the soil microorganism groups most studied likely due to its importance as provider mutualist (Omacini et al, 2012; Pieterse et al, 2014), other root colonizers (e.g., Trichoderma spp., Piriformospora indica , Penicillium spp.)…”
Section: Introductionmentioning
confidence: 99%